ANALISIS KEUANGAN PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEC (JII) BURSA EFEK INDONESIA PERIODE TAHUN 2011-2014 - Cahyaningtyas, Niken Wahyu (PERMANA, 2015)
The purpose of this study was to test the profitability analysis simultaneous effect on stock prices of companies listed in the Jakarta Islamic Index (JII) listing on the Indonesian Stock Exchange (BEI) and which variables that have the most impact on stock. The data used in this research is secondary data obtained from the Indonesian Capital Market Directory (ICMD). The data are financial statements that contain financial ratios ROA, ROE, EPS, NPM and the closing share price (closing price) for the years 2011-20113. The results of the hypothesis test showed the value of F test of 4994 and in 0003, which means a significant independent variable ROA, ROE, EPS and Company NPM simultaneously affect the dependent variable stock price. Because the F test shows significant value 0.003 <0.05 which means that any changes in the independent variables will affect the companys stock price in Jakarta Islamic Index (JII) that listing on the stock exchanges in Indonesia. ROA has a significant negative impact on stock prices, ROE has a positive impact is not significant to the stock price, EPS has no significant negative effect on stock prices. Results of the study were not significant among the variables EPS due to the fluctuations in the data EPS, NPM has a positive effect not significant effect on stock prices.Keyword:Return on Asset (ROA), Return On Equity (ROE), Earning Per Share (EPS), Net Profit Margin (NPM)